Replacement of corn by cassava meal in broiler rations - Sebastiá, José M.; Lopez, Jorge; Martins, Eli S.; Oliveira, Waldemar M.; Collares, Ary (Pesquisa Agropecuaria Brasileira, 2014)
A trial evaluating cassava meal as corn replacement at 0,10, 20, 30, 40 and 50% level in broiler rations, was conducted at the Montenegro Experimental Station, Rio Grande do Sul, . Brazil. Feed consumption was not affected by replacing corn by cassava meal at levels varying from 0 to 50%. Nine week broilers were significantly heavier for the groups receiving rations in which cassava meal replaced 0, 10, 20 or 30% of the corn than for the 50% replacement group. There were no significant differences in feed conversion among treatment groups.